PENTINGNYA PENDIDIKAN POLITIK BAGI MASYARAKAT DALAM PEMILIHAN KEPALA DAERAH SERENTAK TAHUN 2024 - Munte, Herdi; Sagala, Christo Sumurung Tua (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Political education plays a crucial role in strengthening the quality of democracy and increasing public participation in Indonesia’s 2024 Simultaneous Regional Elections. Through political education, citizens can gain a comprehensive understanding of their rights and obligations, enabling them to exercise their voting rights wisely, rationally, and responsibly. This study employs a normative legal research method using statutory, conceptual, and historical approaches to examine the importance of political education and the role of political parties in promoting political awareness among citizens. The findings indicate that political education significantly helps prevent money politics, reduce social conflict, and strengthen the legitimacy of election results. Moreover, continuous political education contributes to producing regional leaders with integrity and fostering democratic, transparent, and accountable governance.Keywords: Political Education, Public Participation, Regional Elections 2024.